Correction: Development of a WS2/MoTe2 heterostructure as a counter electrode for the improved performance in dye-sensitized solar cells. Issue 2 (11th January 2019) - Hussain, Sajjad; Patil, Supriya A.; Memon, Anam Ali; Vikraman, Dhanasekaran; Abbas, Hafiz Ghulam; Jeong, Sung Hoon; Kim, Hyun-Seok; Kim, Hak-Sung; Jung, Jongwan
Abstract : Correction for 'Development of a WS2 /MoTe2 heterostructure as a counter electrode for the improved performance in dye-sensitized solar cells' by Sajjad Hussain et al., Inorg. Chem. Front., 2018, 5, 3178–3183.